Research Progress and Future Development on Mission Planning Technologies of Planetary Rover. (2015) - Qiong, Wang; Dengyun, Yu; Yang, Jia
Abstract: Roving exploration becomes a major method of further exploration to target planet after preliminary circling exploration. Mission planning is to search feasible action sequence and trajectory of the rover from initial state to target state, satisfying complex constraints such as terrain, energy, thermal control and communications. Hence it is the basis and key of controlling rover to explore the planet safely and effectively. Global path planning and local path planning could be seen as a special case of mission planning. In this paper existing planetary rovers, prototypes and related navigation technologies are briefly summarized, followed by an introduction of various mission planning algorithms. Finally several areas for future research are specified.